Good is also Banal: on "stille Helden" and Literature - Martín Martín, Juan Manuel (Revista de Filología Alemana, 2013)
An indeterminate number of people from the most diverse backgrounds collaborated to help hundreds of Jews escape their extermination. An inconvenience for post-war German society, it is not until the 1990s, with the beginning of a new context brought about by the new political environment, that we begin to see some attention paid to these people. Proof of such is found in the presence of this subject in scientific and informative literature as well as in commemorative literature and fiction. These persons are often referred to as stille Helden (Silent Heroes), a recognition they frequently reject as they do not consider their actions to have been the result of heroic intentions, rather the only possible reaction to what was happening around them. During a time of moral confusion, Good, for a few, was as banal as Evil for the great majority.
Keywords: Stille Helden; Oskar Schindler; Cultural Memory; Holocaust; Contemporary German Literature.